Eﬀect of posterior tibial slope and implant material on the bone-implant system following TKA: A finite element study. Issue 1 (1st January 2018) - Baliga B, Ravishanker; Pai B, Raghuvir; Shenoy, Satish; Hegde K, Atmananda; Rao K, Sharath; Swaroop, Shubham; Shetkar, Abhijeet
Abstract: A posterior stabilized type of total knee replacement (TKR) device was used to assess the impact of material of tibial tray and varying posterior tibial slopes on the periprosthetic bone region. Two type of tray material viz. all-polyethylene (AP) metal-backed (MB) and four posterior tibial slopes (0 °, 3 °, 5 ° and 7 ° ) were considered in a subject-specific finite element full tibia bone model. The strain responses in periprosthetic bone region due to tibial material and over the length of tibial tray keel was investigated under peak axial loads of walking and stair descending/ascending. The anticipated increment in bone density owing to implantation for the cases considered was additionally displayed. The impact of stress shielding on the periprosthetic bone was found to be more fundamentally affected by the material used than its geometry. Considerably higher stress shielding was observed in MB cases than on its AP equivalent, especially in the region underneath the baseplate. Hence, the effect of material is found to have greater impact on the regions assessed than the posterior tibial slopes considered.